2020
DOI: 10.32615/ps.2020.029
|View full text |Cite
|
Sign up to set email alerts
|

Light reacclimatization of lower leaves in C<sub>4 </sub>maize canopies grown at two planting densities

Abstract: C4 plants have high photosynthetic capacity but are inefficient under low light. In a canopy, lower leaves developed under high light are progressively shaded. To elucidate how lower leaves in a C4 canopy reacclimatize to low light, we investigated maize canopies differing in light environment grown at standard and low planting densities (SPD, LPD). Although upper leaves at SPD and both upper and lower leaves at LPD had light-response curves of photosynthesis of sun leaves, lower leaves at SPD had that of shad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…Increased light penetration in the canopy could explain the thicker leaves at ERO, whereas, at HOR, increased shading resulted in higher specific leaf area (Yabiku et al. , 2020) further augmented by high plant density (Table 1) in line with other works (Yang et al. , 2022).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Increased light penetration in the canopy could explain the thicker leaves at ERO, whereas, at HOR, increased shading resulted in higher specific leaf area (Yabiku et al. , 2020) further augmented by high plant density (Table 1) in line with other works (Yang et al. , 2022).…”
Section: Discussionsupporting
confidence: 79%
“…Consistent with this, specific leaf area is decreased in leaves developed at low T (Riva-Roveda et al, 2016;Zhou et al, 2020) and in maize lines from cool temperate regions compared with lines from warmer origin (Verheul et al, 1996). Increased light penetration in the canopy could explain the thicker leaves at ERO, whereas, at HOR, increased shading resulted in higher specific leaf area (Yabiku et al, 2020) further augmented by high plant density (Table 1) in line with other works (Yang et al, 2022). Other factors could also be involved, such as increased leaf sugar accumulation and decreasing specific leaf area which has been reported in leaves developed under lower T (Riva-Roveda et al, 2016).…”
Section: Leaf Traitssupporting
confidence: 59%
“…Net CO 2 exchange rate at a PAR of 2000 μmol m −2 s −1 (close to the maximum attainable midday PAR at the latitude of the experiments) decreased with high PP (P<0.001; Fig. 5B), indicating that mutual shading reduced the photosynthetic potential of the ear leaf (see also Dwyer et al, 1991;Pignon et al, 2017;Yabiku et al, 2020) but showed no correlation with YOR. The net CO 2 exchange rate at a PAR of 0 μmol m −2 s −1 equates to the rate of respiration, and it was notable that this decreased at high PP (Fig.…”
Section: Breeding Has Reduced Ear Leaf Respirationmentioning
confidence: 83%
“…The net CO 2 exchange rate at a PAR of 0 μmol m −2 s −1 equates to the rate of respiration, and it was notable that this decreased at high PP (Fig. 6A; see also Pignon et al, 2017;Yabiku et al, 2020) and with YOR, and an interaction was observed (PP×YOR, P=0.012). We confirmed the trend between respiration and YOR in a set of experiments with plants grown in pots (Fig.…”
Section: Breeding Has Reduced Ear Leaf Respirationmentioning
confidence: 88%
See 1 more Smart Citation